Evaluación de las energías que interactuaron en el área de concesión de la empresa CNEL-Esmeraldas, durante el año 2019 - Lapo González, Robert Alejandro (2022)
Planning the energy supply of the province of Esmeraldas in 2019, involved the search for energy statistics that intervened in the supply, demand and transformation chains. This document provides methodological sheets that allow the reader to obtain energy data from other areas and periods. The methodology created by OLADE for the preparation of energy balances was implemented. The elaboration of the energy balance within the concession area of CNEL-Esmeraldas company, during the base year 2019, had as main focus the data collection, where INEC was distinguished as the primary basis for the management of primary energy data; biomass, obtaining 38.87 kBEP of production of this energy. Also to Ep Petroecuador as an actor provider of secondary energy information, where it was determined that the secondary energy with the highest participation in the province of Esmeraldas during 2019 was fuel oil with 32.1 %. In addition, ARCONEL was recognized as the agency in charge of electricity data management with 209.6 kBEP of production. The energy demand in Esmeraldas in the analysis period was 6236.38 kBEP, with the transportation sector being the largest energy demander in the province with 1555.12 kBEP. The dynamic evaluation of the energy system in accordance with the economy of Esmeraldas is also presented, determining the main economic-energy relations, between the different sectors of the regional economy, taking into account for example the degree of industrial development of Esmeraldas and the standard of living of its inhabitants, where it was learned that each person consumed 921.78 kWh/inhabitant, and the individual contribution of the inhabitants to the economic development of Esmeraldas during 2019, which was 439.52 US$/inhabitant. All these statistics and with a more detailed level were presented to the Decentralized Autonomous Government of the Province of Esmeraldas. Key words: Energy Balance, statistics, OLADE methodology, socioeconomic indicators.